Linear Cryptanalysis of SAFER-256 - Knarik M. Kyuregyan (Изд-во НАН РА)
In this paper linear cryptanalysis of 256-bit block cipher SAFER-256 is presented. SAFER-256 is secure against differential cryptanalysis after 5 rounds.
Keywords: Mathematics; Algorithm